2016
DOI: 10.1128/jvi.02534-15
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary C Fibers Modulate MMP-12 Production via PAR2 and Are Involved in the Long-Term Airway Inflammation and Airway Hyperresponsiveness Induced by Respiratory Syncytial Virus Infection

Abstract: Children with acute respiratory syncytial virus (RSV) infection often develop sequelae of persistent airway inflammation and wheezing. Pulmonary C fibers (PCFs) are involved in the generation of airway inflammation and resistance; however, their role in persistent airway diseases after RSV is unexplored. Here, we elucidated the pathogenesis of PCF activation in RSV-induced persistent airway disorders. PCF-degenerated and intact mice were used in the current study. Airway inflammation and airway resistance were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Conveniently, it allows one to concomitantly measure the acute effects of these exposures. In fact, one of the common uses of the DCP is to assess the degree of responsiveness to aerosolized methacholine in different models of respiratory diseases 20 21 22 23 24 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Conveniently, it allows one to concomitantly measure the acute effects of these exposures. In fact, one of the common uses of the DCP is to assess the degree of responsiveness to aerosolized methacholine in different models of respiratory diseases 20 21 22 23 24 25 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, PAR-2 plays a crucial role in different animal models of intestinal diseases, focal segmental glomerulosclerosis, skin inflammatory diseases, myocarditis, and airway inflammation. [12][13][14][15][16][17][18][19] Recent studies have shown that human corneal epithelial cells express PAR-2. In human corneal epithelial cells, inhibition of PAR-2 by a specific antagonist prevents proinflammatory cytokine production and reduces inflammation induced by Acanthamoeba plasminogen activator, a serine protease secreted by Acanthamoeba trophozoites, that is involved in the pathogenesis of Acanthamoeba keratitis, indicating that disruption of PAR-2 activity might have a major impact on preventing inflammatory responses in Acanthamoeba keratitis.…”
mentioning
confidence: 99%
“…While the HDM-induced asthma possesses the asthmatic characteristics (AHR, airway inflammation and remodeling) similar to those induced by OVA, ozone, and virus; however, the pathological processing to cause these characteristics is likely not the same. For example, ozone and respiratory syncytial virus either fails or only affects some types of inflammatory cells [ 12 , 17 ], but HDM increases all or more types of inflammatory cells in our pilot and previously reported studies [ 9 , 17 , 18 ]. Moreover, HDM induces chronic airway inflammation and remodeling with a multifaceted immune responses initiated in the lungs, but the classical OVA model is more related to acute airway inflammation with the Th2 skewing adjuvant aluminum hydroxide and sensitization originated in the periphery [ 8 ].…”
Section: Introductionmentioning
confidence: 52%
“…After the final exposure, AHR was measured in conscious mice by means of specific airway resistance (sRaw). In brief, the mice were individually placed in the double-chamber to assess sRaw [ 12 ]. The mice were exposed to aerosolized saline (0 mg/ml) and methacholine solutions in a dose-increasing manner (3.125, 6.25, 12.5, 25, and 50 mg/ml; Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation